PENGARUH PEMBERIAN JENIS FESES TERNAK BERBEDA TERHADAP PERTUMBUHAN RUMPUT GAMA UMAMI - Cahaya Utami, Jumaida; Amrullah, Amrullah; Hamdani, Asrul; Yani, Ahmad; Sudirman, Sudirman; Wahyu Satria, Edi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Gama Umami grass is a superior quality grass species currently widely used as livestock feed. This study aimed to determine the effect of different types of livestock feces on the growth of gama umami grass. The study was conducted from January 2026 to March 2026 using a Randomized Block Design (RBD) with 4 treatments and 4 groups. Data analysis was carried out through analysis of plant height, leaf length, leaf width, stem diameter, and number of tillers using a Randomized Block Design (RBD) analysis of variance. The results showed that the highest average values ​​for all variables, such as plant height, ranged from 16.64-24.90 cm/2 weeks, leaf length 11.22-16.12 cm/2 weeks, leaf width 4.17-8.92 cm/2 weeks, stem diameter 2.18-3.17 cm/2 weeks, and number of tillers 1.03-1.57 cm/2 weeks.